Potential mechanisms of Lian-Zhi-Fan solution for TNBS-induced ulcerative colitis in rats via a metabolomics approach - Bai, Junyi; Xiong, Tingting; Wang, Xiao; Cheng, Yanfen; Luo, Ruifeng; Yang, Xiangdong; Fu, Chaomei (Frontiers in Pharmacology, 2022)
Lian-Zhi-Fan (LZF) decoction is a hospital-prescribed traditional Chinese medicine botanical drug prepared by the fermentation of decocted Coptidis Rhizome (Huanglian), Gardeniae Fructus (Zhizi), and alum (Baifan). It has been used clinically in China for the treatment of anal fistula, perianal abscess, ulcerative colitis (UC), and other anorectal diseases for hundreds of years. However, due to the complexity of traditional Chinese medicine, the potential mechanisms of LZF in the treatment of UC have remained unknown. This study primarily investigated the remarkable pharmacological effects of LZF on TNBS-induced UC rats. To explore the complex targets and regulatory mechanisms of metabolic networks under LZF intervention, a metabolomics approach mediated by HPLC/Q-TOF-MS analysis was used to screen the different metabolites and their metabolic pathways in the serum in order to characterize the possible anti-UC mechanisms of LZF. After rectal administration of LZF for seven consecutive days, significant amelioration effects on body weight loss, DAI score, and colon inflammation were found in UC rats. Based on this, further metabolomics identified 14 potential biomarkers in the treatment of UC with LZF, of which five possessed diagnostic significance: L-alanine, taurocholic acid, niacinamide, cholic acid, and L-valine. These metabolites are mainly involved in 12 metabolic pathways, including nicotate and nicotinamide metabolism, glycospholipid metabolism, arginine and proline metabolism, primary bile acid biosynthesis, and pantothenate and CoA biosynthesis. These metabolic pathways suggest that LZF ameliorates UC by regulating amino acid metabolism, fat metabolism, and energy production. This study provides a useful approach for exploring the potential mechanisms of herbal prescription in UC treatment mediated by metabolomics.